New near-infrared absorbance peak for inhibitor content detection in transformer insulating oil - Leong Y.S.; Ker P.J.; Jamaludin M.Z.; Nomanbhay S.M.; Ismail A.; Abdullah F.; Looe H.M.; Shukri C.N.S.M. (Elsevier B.V., 2023)
Chemical detection; Corrosion inhibitors; Fourier transform infrared spectroscopy; Infrared devices; Infrared spectroscopy; Insulating oil; Insulation; Mean square error; Power transformers; Absorbance spectrum; Content detection; Effective measures; Inhibitor concentration; Near-infrared waveband; Optical absorbance; Optical spectroscopy; Root mean square errors; Oil filled transformers